Hair coat properties of donkeys, mules and horses in a temperate climate. (8th November 2017) - Osthaus, B.; Proops, L.; Long, S.; Bell, N.; Hayday, K.; Burden, F.
Summary: Background: There are clear differences between donkeys and horses in their evolutionary history, physiology, behaviour and husbandry needs. Donkeys are often kept in climates that they are not adapted to and as such may suffer impaired welfare unless protection from the elements is provided. Objectives: To compare some of the hair coat properties of donkeys, mules and horses living outside, throughout the year, in the temperate climate of the UK. Study design: Longitudinal study. Methods: Hair samples were taken from 42 animals: 18 donkeys (4 females, 14 males), 16 horses (6 females, 10 males) and eight mules (5 females, 3 males), in March, June, September and December. The weight, length and width of hair were measured, across the four seasons, as indicators of the hair coat insulation properties. Results: Donkeys' hair coats do not significantly differ across the seasons. All three measurements of the insulation properties of the hair samples indicate that donkeys do not grow a winter coat and that their hair coat was significantly lighter, shorter and thinner than that of horses and mules in winter. In contrast, the hair coats of horses changed significantly between seasons, growing thicker in winter. Main limitations: The measurements cover only a limited range of features that contribute to the thermoregulation of an animal. Further research is needed to assess shelter preferences by behavioural measures, and absolute heat loss via thermoimaging. Conclusions: Donkeys, and to a lesser extent mules, appear not to be as adapted to colder, wet climates as horses, and may therefore require additional protection from the elements, such as access to a wind and waterproof shelter, in order for their welfare needs to be met.